Improving the Characteristics of Edible Film Using Modified Cassava Starch Over Ethanol Precipitation - Nazarudin; Ulyarti; Indra Agung Pratama; Suripto Dwi Yuwono (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2023)
Cassava starch has been widely explored as film forming material, however its hydrophilicity restricts its application. Hydrophobic material such as modified starch can be used in the film elaboration to improve its quality. This study aims to examine the effect of modified cassava starch concentration on the physical, barrier, and mechanical properties of edible films. A completely randomized design was used with 5 concentrations of modified starch at 0%, 5%, 10%, 15%, and 20% and 4 repetitions to obtain a total of 20 experimental combinations. The ANOVA showed that the modified starch concentration affected the compressive strength, thickness, transparency, and solubility of the edible film, but has no effect on its water vapor transmission rate (WVTR). Usage of 20% modified starch gave the product with the best characteristics at 0.22 mm thickness, 89.45 N/m2 strength, 6.484%/mm transparency, 52.19% solubility, and 21.00 g/m2.hour WVTR.